2020
DOI: 10.3390/f11030320
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground Biomass Allometric Models for Evergreen Broad-Leaved Forest Damaged by a Serious Ice Storm in Southern China

Abstract: A catastrophic ice storm occurred in the spring of 2008, which severely destroyed nearly 13% of China’s forests; among them, the broad-leaved forest suffered the most extensive damage. In this study, allometric models of the evergreen broad-leaved forests damaged at different recovery stages after the disaster were established to estimate the aboveground biomass of damaged trees. Plant plots were established and surveyed in damaged forests to determine species composition and diameter distribution, and finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Thus, the lower H max and increased growth elasticity in China could be related to the combined climatic and soil properties, management histories, compositional species pool or past disturbances (Zhao et al 2009, 2013, Zhang et al 2014, Ni et al 2015, Cai et al 2020, Mao et al 2020), as already reported between wet and moist forests in global‐scale studies (Tao et al 2016, Zhang et al 2016). Similar trends were reported between frequently disturbed and undisturbed primary forests at local and regional scales (Thomas et al 2015, Tong et al 2020, Zhao et al 2020), suggesting a combined environmental and disturbing controls of tree allometry.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Thus, the lower H max and increased growth elasticity in China could be related to the combined climatic and soil properties, management histories, compositional species pool or past disturbances (Zhao et al 2009, 2013, Zhang et al 2014, Ni et al 2015, Cai et al 2020, Mao et al 2020), as already reported between wet and moist forests in global‐scale studies (Tao et al 2016, Zhang et al 2016). Similar trends were reported between frequently disturbed and undisturbed primary forests at local and regional scales (Thomas et al 2015, Tong et al 2020, Zhao et al 2020), suggesting a combined environmental and disturbing controls of tree allometry.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, evergreen forests should dominate realistic ecological conditions and outperform deciduous forests in wet, warm, and light‐limited environments (Givnish 1988, 2002, Way and Oren 2010). The evergreen trees dominating central southern subtropical forests and eastern and middle‐low‐elevation conifer continental forests of China seemingly confirm this hypothesis, and the predefined patterns differ from those of other forests worldwide (Ge and Xie 2017, Zhao et al 2020). However, few studies have reported wide comparisons across levels of continental forests and tree species at functional biogeographical scales.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations